TEACHER TRAINING IN BRAZIL: An Analysis of Studies on State Continuing Training Centers (Global Journal of Human-Social Science, 2024)
Abstract not found
Keywords: centros estaduais de formação continuada; formação continuada de professores; concepções teóricas e metodológicas